THE ARTISTIC PARADIGM OF CULTURAL EDUCATION - Voronova Nadiуa (Educological discourse, 2018)
In the article rethinking the integration of culture and art in the educational space. Explores cultural training which described the art. The purpose of this article is to identify and analyze the artistic paradigm of cultural education. The first paradigm is defined the common understanding of artistic culture. She interprets artistic culture in the historical aspect. Based on the work of prominent philosophers, teachers, he first, art historians, highlighted important issues as: the development impact of art on the formation of оutlook, moral realm, psychological culture, development of self-consciousness. Art, embodying human ideals and resulting values, however, is not limited to this. It vividly simulates the experience of human existence in its totality. The second feature paradigm in cultural education is highlighted, as the development of art pedagogy. The paradigm is based on the development problems of using art in the educational process in the conditions of mass education, takes into account different age groups of children and young people; the different conditions of its implementation. Perspective is determined by the fact that art activities offer solutions to a number of socio-psychological and pedagogical problems. Among them, such as: creative expression and development; constructive expression of emotions, getting rid of emotional stress; the development of consciousness and cognitive activity; the experience of social interaction. The third artistic paradigm in cultural education – art as a means of aesthetic education. Actively developed methods of using art in relation to art education in their spare time and the development of creativity in terms of leisure activities of a mass character. Classes in Amateur art collectives allowed to solve a number of socio-psychological problems of youth. Among them is creation of conditions for realization of the needs of the young person in the initiative, individual self-assertion; splash excess energy in socially relevant forms; the identification of creative potential, development of artistic abilities; the development of communicative qualities, discipline. In the conclusions it was noted that perspective is the introduction of multimedia technologies in the theory and methods of professional training of future masters of cultural studies.